Risk Factors Underlying COVID-19 Lockdown-Induced Mental Distress - Novotný, Jan Sebastian; Gonzalez-Rivas, Juan Pablo; Kunzová, Šárka; Skladaná, Mária; Pospíšilová, Anna; Polcrová, Anna; Medina-Inojosa, Jose Ramon; Lopez-Jimenez, Francisco; Geda, Yonas Endale; Stokin, Gorazd Bernard (Frontiers in Psychiatry, 2020)
Recent reports suggest that the COVID-19 lockdown resulted in changes in mental health, however, potential age-related changes and risk factors remain unknown. We here measured COVID-19 lockdown-induced stress levels and severity of depressive symptoms prior to and during the COVID-19 lockdown in different age groups and then searched for potential risk factors in a well-characterized general population-based sample. A total of 715 participants were tested for mental distress and related risk factors at two time-points, baseline testing prior to COVID-19 and follow-up testing during COVID-19, using a battery of validated psychological tests including Perceived Stress Scale and Patient Health Questionnaire. Longitudinal measurements revealed that prevalence of moderate to high stress and severity of depressive symptoms increased by 1.4- and 5.5-fold, respectively, during the COVID-19 lockdown. This surge in mental distress was more severe in females, but present in all age groups with the older age group exhibiting cross-sectionally the lowest levels of mental distress prior to and during the lockdown. Illness perception, personality characteristics such as feeling of loneliness and several lifestyle components have been found associated with significant increase in mental distress. The observed changes in mental health and identified potential risk factors underlying these changes provide critical data justifying timely and public emergency tailored preventive, diagnostic and therapeutic mental health interventions, which should be integrated into future public health policies globally.